Exploring Stakeholders’ Support in an International Equity Placement Strategic Alliance - Harimukti Wandebori; Harm-Jan Steenhuis; Aard J. Groen (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
An International Equity Placement Strategic Alliance (IEPSA) is a strategic alliance of shared ownership between partners of different nationalities. In 1998, the Indonesian government initiated the IEPSA to privatize its State-Owned Enterprises (SOE). Problems arose due to the lack of stakeholders’ support, although it was able to improve the performance of the SOE. Variables within the stakeholders’ support and the relationship among stakeholders were the keys to bring the IEPSA into prevalence; they comprised of its transparency, share price, the degree of the internal relationship, fulfilment of the budget deficit, company restructuring, unprecedented moment, restricted shares in the market, the existence of the floor price, and the plan for the IEPSA. The research reveals that the dimensions of the share price and the degree of the internal relations are the required bases for the government to formulate and implement a strategy to secure the stakeholders’ support (involvement) using the matrix of a general strategy to secure their support.